2021
DOI: 10.1111/aor.14068
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil dysfunction due to continuous mechanical shear exposure in mechanically assisted circulation in vitro

Abstract: Objective: Leukocytes play an important role in the body's immune system. The aim of this study was to assess alterations in neutrophil phenotype and function in pump-assisted circulation in vitro. Methods:Human blood was circulated for four hours in three circulatory flow loops with a CentriMag blood pump operated at a flow of 4.5 L/min at three rotational speeds (2100, 2800, and 4000 rpm), against three pressure heads (75, 150, and 350 mm Hg), respectively. Blood samples were collected hourly for analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Our group previously reported increased levels of neutrophil activation (i.e., elevation in MAC-1 and decline in CD62L and CD162) in an in vitro circulation loop using human blood with a CentriMag pump (Abbott Inc, Chicago, IL) over time. 18 Using a Couette-type blood-shearing device, we also showed an augmentation in neutrophil activation (i.e., elevation in MAC-1 and decline in CD62L but not CD162) with increasing levels of shear stress after only 0.5 s of exposure. 19 Pieper et al found a similar trend of neutrophil activation when they used ovine blood in an in vitro loop with the CentriMag VAD to evaluate the leukocyte activation and damage caused by the pump over a 6-h circulation.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Our group previously reported increased levels of neutrophil activation (i.e., elevation in MAC-1 and decline in CD62L and CD162) in an in vitro circulation loop using human blood with a CentriMag pump (Abbott Inc, Chicago, IL) over time. 18 Using a Couette-type blood-shearing device, we also showed an augmentation in neutrophil activation (i.e., elevation in MAC-1 and decline in CD62L but not CD162) with increasing levels of shear stress after only 0.5 s of exposure. 19 Pieper et al found a similar trend of neutrophil activation when they used ovine blood in an in vitro loop with the CentriMag VAD to evaluate the leukocyte activation and damage caused by the pump over a 6-h circulation.…”
Section: Discussionmentioning
confidence: 59%
“…21 Previously, our in vitro study showed that the CentriMag pump caused an initial increase in neutrophil phagocytic capacity in the device-assisted circulation at 1 h followed by a subsequent decline for up to 4 h in a rotational speeddependent manner. 18 We show that in patients without a bridge device, inflammatory cytokines (IL6, IL8, and TNF-α, but not IL1) increased by POD3 and normalize after 2 weeks. Similarly, a previous study reported an elevation in TNF-α, IL6, and PMN elastase throughout the entire 12-week follow-up period.…”
Section: Discussionmentioning
confidence: 65%
“…The few in-vitro studies that have been published show leukocyte morphological changes, reduced lifecycle, diminished cell immunity, surface receptor loss, activation, and cell fragmentation after exposure to HMSS. 7,10–12 These leukocyte alterations have also been reported in vivo in clinical studies of LVAD patients. Reduced leukocyte count, compromised cellular immunity, increased leukocyte-platelet aggregates, cellular fragmentations, microparticle generation, and leukocyte activation were reported.…”
mentioning
confidence: 62%
“…The pressure heads for three modes at the flow rate of 4.5 L/min can reach 75, 150, and 350 mmHg, respectively. 19…”
Section: Methodsmentioning
confidence: 99%